2015
DOI: 10.1186/s12889-015-1351-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the epidemiology of laboratory-confirmed influenza A and influenza B cases in Manitoba, Canada

Abstract: BackgroundDespite the public health significance of annual influenza outbreaks, the literature comparing the epidemiology of influenza A and B infections is limited and dated and may not reflect recent trends. In Canada, the relative contribution of influenza A and B to the burden of morbidity is not well understood. We examined rates of laboratory-confirmed cases of influenza A and B (LCI-A and LCI-B) in the Canadian province of Manitoba between 1993 and 2008 and compared cases of the two types in terms of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
5
5
1
Order By: Relevance
“…However, the patterns observed are in line with previous studies15222324, which reported different severity of influenza A (H1N1pdm) or influenza B between Europe and North America. In our study, we considered both 2,000 and 500 confirmations as thresholds.…”
Section: Discussionsupporting
confidence: 92%
“…However, the patterns observed are in line with previous studies15222324, which reported different severity of influenza A (H1N1pdm) or influenza B between Europe and North America. In our study, we considered both 2,000 and 500 confirmations as thresholds.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies comparing demographic attributes of patients with influenza A and B, a higher age for patients with influenza A was described although this may vary according to influenza A strains. Patients with H3N2 were shown to be older than influenza B patients while patients with H1N1 tended to be younger than patients with influenza B [21][22][23]. A French study by Chagvardieff et al analyzed patients presenting at an emergency department and similarly to the present results influenza B patients were significantly older [24].…”
Section: Discussionsupporting
confidence: 76%
“…Unfortunately, no information was available about influenza subtypes in the current population; however, during the season concerned influenza A/H1N1 and influenza B/Yamagata were the dominant subtypes in Austria [25]. It has been shown that patients with influenza A suffered more often from chronic diseases, such as asthma, chronic obstructive pulmonary disease, diabetes and cardiovascular disorders [22,27]. Furthermore, patients with influenza A were more likely to be smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Following duplicate removal (N = 946) and the screening of titles and abstracts (N = 5787), a total of 43 records were deemed to be worthy of further evaluation and the corresponding full texts were assessed. Of these, 16 papers met all inclusion criteria and were included. In the study by Caini et al only 12 of 26 study locations had a sufficient number (≥100) of isolates among the elderly.…”
Section: Resultsmentioning
confidence: 99%